SiRNA high throughput screening identifies regulators of chloropicrin and hydrogen fluoride injury in human corneal epithelial cell models. (September 2022) - Ruff, Albert L.; Causey, Robert D.; Koenig, Jeffrey A.; LaGrasta, Cristina V.; Gomez, Amber M.; Chalmers, Bailey T.; Lehman, John G.
Abstract: Corneal injuries induced by various toxicants result in similar clinical presentations such as corneal opacity and neovascularization. Many studies suggest that several weeks post-exposure a convergence of the molecular mechanisms drives these progressive pathologies. However, chemical agents vary in toxicological properties, and early molecular responses are anticipated to be somewhat dissimilar for different toxicants. We chose 3120 targets from the Dharmacon Human Druggable genome to screen for chloropicrin (CP) and hydrogen fluoride (HF) corneal injury as we hypothesized that targets identified in vitro may be effective as therapeutic targets in future studies. Human immortalized corneal epithelial cells (SV40-HCEC) were used for screening. Cell viability and IL-8 were analyzed to down-select hits into validation studies, where multiplex cytokine analysis and high content analysis were performed to understand toxicant effect and target function. Some endpoints were also evaluated in a second human immortalized corneal epithelial cell line, TCEpi. Over 20 targets entered validation studies for CP and HF; of these, only three targets were shared: NR3C1, RELA, and KMT5A. These findings suggest that early molecular responses to different toxicants may be somewhat distinctive and present dissimilar targets for possible early intervention. Highlights: siRNA high throughput (HTS) screening is an efficient way to assess gene function. Chloropicrin (CP) and hydrogen fluoride (HF) exposure cause severe corneal injuries. siRNA HTS was used to assess early regulators of toxicant-induced corneal injury. Early molecular responses to different toxicants appear to be largely dissimilar. Early treatments may need to be toxicant-specific.